PENGARUH PROFITABILITAS, KESEMPATAN INVESTASI, FREE CASH FLOW, DAN DEBT POLICY PADA KEBIJAKAN DIVIDEN PERUSAHAAN MANUFAKTUR - Wulandari, Dessy Ulfa; Suardana, Ketut Alit (E-Jurnal Akuntansi; Vol 20 No 1 (2017), 2017)
The purpose is to find out which influence profitability, investment opportunities, free cash flow, and debt policy on dividend policy. The population is manufacturing companies were listed on the Indonesia stock exchange period 2011-2014. The number of sample 21 company in 4 years of observations obtained 84 total observations with purposive sampling technique. The analysis of the data used in this study is multiple linear regression analysis. The study found that significant negative effect on the profitability of the dividend policy. Investment opportunities significant negative effect on the dividend policy. Free cash flow significant positive effect on the dividend policy. Debt policy significant negative effect on the dividend policy. Based on the value of R 2 values obtained 0.356 meaning the great influence of the independent variable on the dividend policy can be explained by a model equation of 35.6%. The rest of 64.4% is affected by other factors.
Keywords: Profitability, Investment Opportunities, Free Cash Flow, Debt Policy, and Dividend Policy.